AN OVERVIEW OF THE IMPLEMENTATION OF MUSICAL DRAMA IN THE INTRODUCTION TO LITERATURE COURSE - Rahman, M Arinal; Jamalullail, Jabal; Handrianto, Ciptro (Indonesian Journal of Educational Assessment, 2021)
The performance of musical drama is critical to implement in the classroom, especially for introduction to literature subject. Since this activity relates to art and literature, students might be interested in learning an introduction to literature with a performance that is amusing their motivation and interest. This paper provides information about how crucial musical drama is, the definition of musical drama, its procedure in the classroom, the aspects that should be applied to the students, familiar genre of song and theme of drama for the performance, the scoring system or rubric, the influence of musical drama for students’ development, the advantages and disadvantages contained in musical drama performance, and the urgency. This paper also reviews the previous study about musical drama performance, which is applied by art and literature teachers in the classroom to increase the motivation of students to learn literature.